Provisional Agenda for the Twenty-Ninth Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The following is the provisional agenda for the Twenty-Ninth Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on April 11, 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: HQ2 Conference Hall; Policy Agenda; Policy Coherence; PP